Recuperative Energy Potential From A Typical Landfill In Malaysia. - Ting, Ming Chung; Saad, Abdul Yamin (2008)

(untitled)
The study looks into availability of recuperative energy potential from a typical landfill in Malaysia. Due to the rapid urbanization, rising population and lifestyle changes, the amount of municipal solid wastes (MSW) in Malaysia is increasing year by year.